PERJANJIAN PEMBORONGAN PEKERJAAN JALAN PARIT ANTARA CV. MUSI RAYA DENGAN DINAS PEKERJAAN UMUM KABUPATEN TANJUNG JABUNG BARAT. - M Chairul Idrah (Universitas Batanghari Jambi, 2010)
Government through kimpraswil authority and responsibility to improve and make a highway or public road, but to the success and transparency in the use of project funds road, the road works are handed over to private parties are reputable and trustworthy quality and ability, as also occurred in the archipelago Cape District Tanjung Jabung Barat.Although in the letter agreement which has been agreed by the parties determined the rights and obligations of each - each party and should be implemented fully and consistently, but in reality there is a highly undesirable, the existence of deficiencies or incompatibility with the existing provision is clearly an act of default (broken promise) that harm either party.The existence of a default in the execution of the agreement was allegedly also occurred in the implementation of street paving work chartering agreement trench made by the Public Works Department of West Tanjung Jabung premises CV. Musi Raya. The occurrence of default in the execution of employment agreement that they will conduct detrimental to either party, be it the loss cost, time or energy. Breach that occurred was very possible because of the constraints faced.Keyword : agreement, breach of contract